Makna Religiusitas dalam Puisi Ebbhu Karya Sugik Muhammad Sahar: Studi Hermeneutika Paul Ricoeur - Moh. Tabarok; Ari Ambarwati; Akhmad Tabrani (Indonesian Language Education and Literature, 2025)
Penelitian ini bertujuan untuk mendeskripsikan nilai-nilai religius dalam puisi Ebbhu karya Sugik Muhammad Sahar yang berhubungan dengan masyarakat Madura serta interpretasi nilai-nilai religius berdasarkan pendekatan hermeneutika Paul Ricoeur. Pengumpulan data dilakukan melalui studi pustaka. Analisis data mengikuti prosedur hermeneutika Ricoeur yang meliputi: (1) distansiasi (pembacaan objektif teks); (2) interpretasi (pemaknaan simbol dan metafora); (3) apropriasi (kontekstualisasi makna); dan (4) referensi (penemuan makna di balik teks). Hasil penelitian menunjukkan adanya nilai religiusitas dalam puisi Ebbhu karya Sugik Muhammad Sahar. Nilai-nilai religius ini berhubungan dengan nilai keagamaan yang terdapat pada masyarakat Madura seperti ketaatan dalam beribadah (ubudiyah), penghormatan terhadap nilai-nilai spiritual (ta’dzim), pencarian ilmu pengetahuan (tholabul ’ilmi), dan keteguhan dalam menjalankan ajaran agama (istiqomah).The Meaning of Religious in The Poetry Ebbhu by Sugik Muhammad Sahar: Poul Ricour's Hermeneutic StudiesThis study aims to describe the religious values in Sugik Muhammad Sahar's Ebbhu poem related to Madurese society and the interpretation of religious values based on Paul Ricoeur's hermeneutic approach. Data collection was conducted through literature study. Data analysis followed Ricoeur's hermeneutic procedures which included: (1) distanciation (objective reading of the text); (2) interpretation (meaning of symbols and metaphors); (3) appropriation (contextualization of meaning); and (4) reference (discovery of meaning behind the text). The results of the study showed the existence of religiosity values in Sugik Muhammad Sahar's Ebbhu poem. In addition, these religious values are related to religious values found in Madurese society such as obedience in worship (ubudiyah), respect for spiritual values (ta'dzim), seeking knowledge (tholabul 'ilmi), and steadfastness in carrying out religious teachings (istiqomah).